STRATEGI PENGEMBANGAN USAHA PENYEWAAN SOUND SYSTEM PADA PLAY SOUND YOGYAKARTA - FEBRA SIANIPAR (Harmoni: Jurnal Pemikiran Pendidikan, Penelitian Ilmu-ilmu Seni, Budaya dan Pengajarannya, 2018)
This research discusses the strategy of developing a sound system rental company by doing case study on Play Sound Yogyakarta. The strategy in question is the creation of a unique and valuable way, involving a different mindset of an activity. The research methodology used is a quantitative methodology based on SWOT analysis and IE matrix. The results of the analysis show that the variables that become the strength is the most complete equipment show, rent the small and large scale sound, the best service, cooperative relationship with many parties. The disadvantages are limited experts, non-permanent employees, expensive maintenance fees, not well-known brand image. Opportunities are many events need sound, a priority for national events, the existence of marketing through social media. The threat is the emergence of new competitors, the number of competitors make the price below standard. Factor analysis of IE shows in the position of cell IV that grow and build (growth and build). Suitable strategies are intensive (market penetration, market development and product development) or integration (backward integration, forward integration and horizontal integration).